A garantia à convivência familiar e comunitária de adolescentes e jovens no contexto do Serviço de Acolhimento em Família Acolhedora - Cerutti, Neusa Eli Figueredo (2022)
The Welcoming Family Service (SFA) is expressed in the context of the right to family and community coexistence of children and adolescents. In Brazil, this theme gains centrality with the Federal Constitution (CF) of 1988. From there, social policies begin to insert the aforementioned guideline, of the right to family and community coexistence, in their formulation and implementation process; among them, the policy of attention to children and adolescents stands out, which understands the family, regardless of its configuration, as an a priori locus, in which there must be care and respect for the individuality of its members. The Child and Adolescent Statute (ECA) (1990) presents family and community coexistence as the unifying element of the principle of integral protection, a condition that has marked the agendas of events and theoretical academic discussions. Although this measure is legally foreseen for children and adolescents between 00 and 18 years of age, some Brazilian experiences have successfully expanded and intensified the measure for adolescents and young people between 18 and 21 years of age, arousing interest in carrying out the present research that has as its theme the Guarantee of Family and Community Coexistence of Adolescents and young people in the context of the Shelter Service in a Shelter Family, considering above all the significant number of adolescents and young people who currently live in shelters in the country, on average of 15 thousand based on in the Census / SUAS / 2019. For this, the research chose as a guide the following question: what are the limits and possibilities for the implementation of the foster care service in a welcoming family for adolescents and young people. The time frame of the research comprised the years 2015 to 2019. In this sense, this Dissertation had the general objective of identifying the limits and possibilities for the implementation of the foster care service in a welcoming family for adolescents and young people. The research is configured as bibliographic, documental and field research, in which the data analysis methodology was of a quantitative-qualitative nature. The bibliographic research sought knowledge of the theme, guaranteeing family life, which is the theoretical framework that guided the analysis of the research results. The documentary research was carried out through the reading and analysis of public documents from the website of the National Council of Justice (CNJ) and the National Adoption and Reception System (SNAA), as well as the Census - Single Social Assistance System (SUAS/)2019. In order to carry out the empirical research, the questionnaire containing eight (08) thematic axes was used as a technique for data collection, aimed at ten (10) professionals, managers of the High Complexity Social Protection (PSE) which were foreseen in the sample and, who agreed to participate in the investigation by answering questions in the questionnaire. It is ensured that throughout the research development process, the integrity and identity of the subjects were preserved, respecting the principles of the Social Worker's Code of Ethics and the norms of the Research Ethics Committee (CEP) of Unioeste. Finally, the work pointed out challenges such as the irregularity of the training of professionals and foster families, little investment by state and federal governments in the implementation and implementation of foster care in a foster family in the municipalities belonging to the sample, as well as the need for discussion about the Plans of Positions, Careers and Salaries (PCCS) of the professionals of (SUAS). The possibilities for guaranteeing the right to family and community coexistence of adolescents and young people depend on better working conditions, investment in qualified human resources, adequate material resources and ethical commitment of all those involved, materialized through behaviors that can anchor socio- affective bonds, capable of guaranteeing that biological ties are not the only way of affection and care.